PENGARUH KEBIJAKAN DIVIDEN, KEPEMILIKAN MANAJERIAL, DAN UKURAN DEWAN DIREKSI TERHADAP KEBIJAKAN HUTANG (Studi pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Nur Febriyana Dewi; Yulia Efni; Andewi Rokhmawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of Dividend Policy,Managerial Ownership and Board of Directorsto the Debt Policy with Firm Size as a control variable. The population in this study was banking companies listed in Indonesia Stock Exchange in the period of 2011-2015. Dependent variable in this study has Debt Policy, while independent variables are Dividend Policy, Managerial Ownership, Board of Directors and Firm Size as control variables. This study had population as many as 45.This study used purposive sampling techniques and the samples included were 29 companies. To analysis the data, this research used are multiple regression by using SPSS version 23.00. The results show that the Dividend Policy,Managerial Ownership, Board of Directorsand Firm Size simultaneously have a significant effect on Debt Policy. Meanwhile partially, Dividend Policy has anegative significant effect on Debt Policy.Managerial Ownership does not have a significant effect on Debt Policy. Board of Directors has a negative significant effect on Debt Policy. Firm Size has a positive significant effect on Debt Policy.Keywords: Debt Policy (DER), Divident Policy (DPR), Board of Directors (BZ) and Firm Size (SIZE).